The last lion, Winston Spencer Churchill : visions of glory, 1874-1932 - Manchester, William, 1922-2004. (Boston : Little, Brown, 1983)
Volume one of a projected three-part biography of Winston Churchill, who grew to manhood in the twilight of the Empire and was elected to Parliament while Victoria still ruled England.
Map on lining papers.
Includes bibliographies and index.
Keywords: Churchill, Winston, -- 1874-1965.; Prime ministers -- Great Britain -- Biography; Great Britain -- Politics and government -- 1901-1936.; Great Britain -- Foreign relations -- 1901-1910.; Great Britain -- Foreign relations -- 1910-1936.